Love, Loss, and Resilience: an in-depth Literary Analysis of 'All the Bright Places' (2015) through the Lens of Existentialism - Titis Setyabudi; Basyir Yasier Rais (PT Publikasiku Academic Solution, 2023)
This in-depth literary analysis explores the novel